2008
DOI: 10.1007/s11605-008-0631-7
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Management of Colonoscopic Perforations

Abstract: Perforations from diagnostic colonoscopy usually are large enough to warrant surgical management, whereas perforations from therapeutic colonoscopy usually are small, leading to successful nonoperative treatment. Over the last decade, the surgical treatment of colonoscopic perforations has evolved, as there has been a trend that favors primary repair versus bowel resection with successful outcome. Careful observation and clinical care adherent to strict guidelines for patients treated nonoperatively is appropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
1
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 17 publications
3
43
1
5
Order By: Relevance
“…Moreover, a retrospective analysis of 35 patients found that emergency laparotomy was required for 88% of diagnostic colonoscopy-associated perforation patients but for only 9% of therapeutic colonoscopy-associated perforation cases [24]. Our findings were similar, in that mean perforation size was larger and emergency laparotomies were needed more frequently for patients with diagnostic colonoscopy-associated perforations.…”
Section: Discussionsupporting
confidence: 69%
“…Moreover, a retrospective analysis of 35 patients found that emergency laparotomy was required for 88% of diagnostic colonoscopy-associated perforation patients but for only 9% of therapeutic colonoscopy-associated perforation cases [24]. Our findings were similar, in that mean perforation size was larger and emergency laparotomies were needed more frequently for patients with diagnostic colonoscopy-associated perforations.…”
Section: Discussionsupporting
confidence: 69%
“…On the other hand, there remain infrequent but potentially catastrophic risks with colonoscopy such as perforation and splenic injury. 4,5 In line with our research, we agree with the authors that focal uptake is worth investigating and other patterns are not. However, a formal modelling and cost-effectiveness analysis may also be required in different health care systems with different policies for funding both FDG-PET scans and screening colonoscopies to properly justify the process.…”
supporting
confidence: 92%
“…Endoscopy-related complications could result from preparation for the procedure (such as hypotension and electrolyte imbalance following mechanical bowel preparation), or they could be directly related to the endoscopic procedures (such as postpolypectomy hemorrhage and colonic perforation). Although colonoscopic perforation (CP) is a rare complication, it is associated with a high rate of morbidity and mortality [1][2][3][4] . The incidence of CP could be as low as 0.02% in diagnostic colonoscopy and could be as high as 0.6% in therapeutic colonoscopy [5,6] .…”
Section: Introductionmentioning
confidence: 99%